Pembuatan batik tulis menggunakan zat warna alami kulit akar mengkudu dengan fiksator symplocos sp. - Mohamad, Falahy; Widadi, Zahir; Maghfiroh, Maghfiroh (Fakultas Teknik Universitas Pekalongan bekerjasama dengan Asosiasi Perajin dan Pengusaha Batik (APPBI), 2024)
The fabric mordanting process usually uses chemicals. The use of chemicals can pollute the surrounding environment. In this case, simplokos leaves can be used as a natural mordant or fixator in the natural coloring process. Apart from that, the process of dyeing natural dyes tends to produce light colors. The process of deploying the 3 layers used in this research is expected to get better results. The dyeing method uses the technique of pounding noni root bark and simplokos leaves repeatedly in three layers of fabric samples, then letting it sit for one week with a dose of 1:3, namely 50g simplokos leaves and 150g noni root bark with the addition of 300 mL of water. The results of the research show that written batik cloth produces a pink print with an insignificant difference in color aging, but the third layer (basic) cloth sample produces a darker color than the other two cloths. In addition, the fabric experiences fading due to the difference in the appearance of final result between the fabric before and after malam removal.